Effectiveness of the Early Warning Score in Enhancing Nurses’ Responsiveness to Critical Patients: A Quasi-Experimental Study in the Emergency Department - Ernawati, Ernawati; Ariani, Sri Purwanti; Pramunika, Pramunika (Journal of Applied Nursing and Health, 2025)
Background: Emergency care services in Indonesia continue to face challenges in quickly identifying patients who are critically ill, which contributes to the high mortality rates in Emergency Departments (ED). While the Early Warning Score (EWS) has been proven effective for early detection of patient deterioration, there are limited studies on its implementation in Indonesian EDs, particularly in provincial hospitals. This highlights a gap in research that needs further attention. Methods: This study used a quasi-experimental design with a pre-test and post-test control group at Dr. H. Moch Ansari Saleh Regional General Hospital, Banjarmasin. Twenty-three ED nurses participated. We measured nurse responsiveness by examining how quickly and accurately they took clinical actions after monitoring EWS. A prototype guideline for using EWS was also developed and integrated into the hospital’s ED reporting system. The research followed CONSORT guidelines for quasi-experimental studies. Results: Most participants were female (60.9%), aged between 19 and 44 years (95.7%), with the majority holding a Diploma III in nursing (65.2%). Before introducing the EWS, 83.3% of nurses in the intervention group responded in one minute or longer, with only 25% accuracy. After the EWS implementation, 91.7% responded in under one minute, with 91.7% accuracy. In the control group, one-minute or longer response times remained high at 90.9%, and accuracy improved slightly from 18.2% to 27.3%. Statistical tests showed significant improvement in response time (p = 0.007) and accuracy (p = 0.005) in the intervention group. Conclusion: Introducing the Early Warning Score improved nurses’ responsiveness in the ED, making their clinical actions faster and more accurate. Integrating EWS into daily practice with clear guidelines can help enable timely interventions and improve patient safety during emergency care.